Banana and bean intercropping: factors affecting bean yield and land use efficiency - Wortmann, Charles S.; Sengooba, T.N.K.; Kyamanywa, S. (Cambridge University Press, 1992)
Beans and bananas were grown in sole crop and intercrop systems for three seasons in 1989 and 1990 to determine the effects of cropping system on diseases, insects and land-use efficiency and the roles of certain bean plant physiological traits on bean yield in the two systems. Bean yield in the intercrop system was 52% of bean sole crop yield. Shading reduced yield, but stem starch levels, chlorophyll content and the chlorophyll a:b ratio were not related to seed yield in either system. Leaf area index was linearly related to yield in the intercrop system, suggesting that a higher plant density may result in higher yields. Nutrient concentration levels in the foliar tissues indicated that low potassium and high manganese availability constrained intercrop bean yield. Leaf manganese levels were higher in beans grown under bananas, reaching levels normally considered toxic for beans. Competition for other nutrients did not appear to affect bean yield. Apparently, interspecies competition for soil moisture did not much reduce bean yields as moisture levels did not differ with cropping system. Disease and insect pest levels were similar for the two bean production systems. Banana yields were associated with potassium levels in the soil. Bananas appeared to be more competitive than beans in the intercrop system. The land equivalent ratio of the banana and bean intercropping system over the three seasons was 1.60.